Present-Biased Individuals, Optimal Paternalism, and Transfers in Kind - Jes Winther Hansen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2005)
Present-biased preferences cause distortions in consumption that can motivate the use of paternalistic in-kind transfers. Empirically, goods are consumed to different degrees when consumption outlay changes. Economists distinguish between necessary goods and luxury goods. A present-biased individual has an intertemporal distortion of consumption toward the present, which in turn distorts present consumption toward luxury goods. In-kind transfers of necessary goods, such as food stamps, can alleviate the intertemporal distortion and make present-biased transfer recipients better off. Further, transfers in kind are asymmetrical in the sense that they can target present-biased recipients without affecting fully rational recipients.
Keywords: D91; H21; H42; I38; 330; in-kind transfers; time preference; Zeitpräferenz; Konsum; Güter; Öffentliche Güter; Ernährungspolitik; Wohlfahrtstheorie